Physical quality and digestibility in vitro determination of green pellet concentrate based on Indigofera zollingeriana - Andi Tarigan; Simon P. Ginting; I. I. Arief; D. A. Astuti; L. Abdullah (Jurnal Ilmu Ternak dan Veteriner, 2017)
This study aims to determine the physical quality and digestibility of green pellet concentrate based on I. zollingeriana. The composition of green pellet concentrate feed contains I. zollingeriana and C. calothyrsus in the following combinations: 1) I. zollingeriana /C. calothyrsus (90/0; R0), 2) I. zollingeriana/C. calothyrsus (75/15; R1), 3) I. zollingeriana/C. calothyrsus (60/30; R2) and 4) I. zollingeriana / C. calothyrsus (45/45; R3). The physical quality study of green pellet concentrate was performed using a completely randomized design with four types of green concentrate as treatments of three replications. Green pellet concentrate studies conducted in vitro rumen fermentation were performed using in a randomized block design with four treatments and three sources of liquid rumen as a block. The results of the experiments conducted with pellet criteria containing I. zollingeriana/C. calothyrsus composition (60/30; R2) have the best physical character (water activity = 0.58; particles size = 12.69 mm; degree value angles = 21.01°; collision endurance = 99.78%; endurance friction = 90.42 %; bulk density = 590 kg/m3) compared to the other treatments. The quality of diet based on digestibility in vitro, dry matter and organic material having a pattern equal to R0 is higher (P<0.05) compared with other treatments, while the rough digestibility of In Vitro protein is seen R0, R1, and R2 (P>0.05), but (P<0.05) was higher than the treatment of R3. There was no difference of pH and total bacteria on green pellet concentrate type. The treatment of R3 has the lowest NH3, VFA and total gas concentration (P<0.5) compared with R2, R1 and R0. It can be concluded that inclusion of Calliandra calothyrsus did not change physical quality of green pellets. However, increasing level of C. calothyrsus increased RUP and reduced digestibility, N-NH3, and total VFA.